HYPOGLYCEMIA IN SICK PRETERM INFANTS AND THE THERAPEUTIC EFFECT OF 12.5% DEXTROSE IN WATER COMPARED WITH 10% DEXTROSE IN WATER - F. Nili M. Ghafuri (Acta Medica Iranica, 2005)
Neonatal hypoglycemia is common and its prompt ‎management is important to reduce neurological sequelae. To determine the effect of two different glucose concentrations of intravenous (IV) fluid ‎therapy in the incidence of hypoglycemia in sick premature infants, 200 preterm infants ‎weighing 1500-2500 g were selected and randomly assigned into two groups. ‎Group 1 received 10% dextrose in water (DW) and for group 2 ‎we used 12.5% DW with recommended fluid volume according to the infant’s condition. ‎First blood glucose sample ‎was obtained during 2-3 hours of life before starting IV therapy and the two others were ‎measured between 4-24 hours of life after starting IV fluid therapy. Plasma glucose < 36 mg/dl during 2-3 hours of life and level below ‎45 mg/dl between 4-24 hours of life were considered as hypoglycemia. ‎Birth weight, gestational age and type of diseases in two groups were matched. Although ‎there was no difference between volume of fluid, statistical differences were found to ‎be significant between amounts of calories (P = 0.000) and dextrose (P = 0.000) received ‎in two groups. We detected 15 and 30 cases of hypoglycemia in group 1 and 2, ‎respectively. After starting IV fluid therapy, the incidence of hypoglycemia decreased especially in ‎group 2 and comparison of cases with two consecutive low plasma glucose in two ‎groups showed significant difference (P= 0.024, relative risk= 2.67). ‎We recommend 12.5% DW when initiation of peripheral IV therapy is indicated in sick ‎preterm infants weighing 1500-2500 g, especially when restriction of fluid is mandated.